Pengembangan Aplikasi Back-End Pemeliharaan Inventaris Pegawai (Studi Kasus : Bappeda Kabupaten Badung) - Winata, Mas Adi; Gede Suhartana, I Ketut (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 7 No 3 (2019): JELIKU Volume 7 No 3, Februari 2019, 2019)
Rapid technological developments make everything workable and integrated with each other. The proper use of Information Technology will increase efficiency in human work. The Regional Development Planning Agency (Bappeda) of Badung Regency as one of the government agencies should have taken advantage of technological advances in various fields of work. Data collection on employee inventory is one of the tasks for employees in the Badung Regency Bappeda. All employee inventories get a maintenance budget or ceiling every year. The use of the ceiling must be accountable, so that recording of inventory maintenance data is very important. So far the data recording is still done manually so it is at risk of errors and lack of work efficiency. Therefore, the authors develop an application that can help inventory data collection and inventory maintenance by adjusting the needs of employees who will become application users. With a system that is integrated with each other and features that are appropriate, Bappeda's Employee Inventory application is expected to facilitate work and reduce errors in data collection on inventory maintenance.